Impaired Formation and Expression of Goal-Directed and Habitual Control in Parkinson’s Disease - Mi, Tao-Mian; Zhang, Wei; McKeown, Martin J.; Chan, Piu (Frontiers in Aging Neuroscience, 2021)
Selective depletion of dopaminergic neurotransmission in the caudal sensorimotor striatum, a subdivision implicated in habitual control, is a major pathological feature in Parkinson’s disease (PD). Here, we evaluated the effects of PD on the formation of goal-directed and habitual control during learning, and for the first time investigated the conflict between these two strategies in the expression of acquired learning. Twenty PD patients and 20 healthy individuals participated in a set of tasks designed to assess relative goal-directed versus habitual behavioral control. In the instrumental training phase, participants first learned by trial and error to respond to different pictured stimuli in order to gain rewarding outcomes. Three associations were trained, with standard and congruent associations mediated predominantly by goal-directed action, and incongruent association regulated predominantly by habitual control. In a subsequent “slips-of-action” test, participants were assessed to determine whether they can flexibly adjust their behavior to changes in the desirability of the outcomes. A baseline test was then administered to rule out the possibility of general inhibitory deficit, and a questionnaire was finally adopted to test the explicit knowledge of the relationships between stimuli, responses, and outcomes. Our results showed that during the instrumental training phase, PD patients had impaired learning not only of the standard and congruent associations (mediated by goal-directed system), but also the incongruent association (mediated by habitual control system). In the slips-of-action test, PD patients responded less for valuable outcomes and more often to stimuli that were associated with devalued outcomes, with poor performance predicted by symptom severity. No significant difference was found between PD and healthy subjects for the baseline test and questionnaire performance. These results collectively demonstrate that the formation of both goal-directed and habitual control are impaired in PD patients. Furthermore, PD patients are more prone to slips of action, suggesting PD patients exhibit an impairment in engaging the goal-directed system with a relatively excessive reliance on habitual control in the expression of acquired learning.